Data collection of the PHYCOB cruise with focus on harmfula algal species in the Southwestern Black Sea in 2021 - Bernd Krock; Urban Tillmann; Kristof Möller; Florian Koch; Fuat Dursun; Laura Boicenco; Oana Vlas; Nina Dzhembekova; Sabri Mutlu; Ertugrul Aslan (PANGAEA, 2024)
The data set was acquired during the PHYCOB cruise in the frame of the Eurofleets+ programme (https://www.eurofleets.eu/2021/10/22/phycob-an-international-oceanographic-expedition-into-the-western-black-sea-coordinated-by-the-alfred-wegner-institut-helmholtz-zentrum-fur-polar-und-meeresforschung-awi/) within the Regional call in the territorrial waters of Romania and Bulgaria in the Western Baltic Sea from 11th to 17th September 2021. The aim of the cruise was to assess the occurrence of potentially harmfal algae and their associated phycotoxins in the Black Sea and the accompanying environmental parameters. Sampling was performed by CTD casts and Rosette water sampling in addition to vertical phytoplankton net hauls from 30 m depth to surface. The determined parameters include the following: Quantitative phytoplankton cell counts in water samples, qulitative determination of toxigenic species next generation sequencing data in plankton net concentrates, monoclonanal cultures established from water sample isolates, phycotoxins in plankton net concentrates, inorganic nitruinets (nitrate/nitrite, phosphate, silicate) , vitamin B12, particulate organic carbon, particulate organic nitrogen, flowcytometry data, and CTD data (temperature, salinity, chlorophyll-a, oxygen, turbidity, radiance).